Lymph node metastases can invade local blood vessels, exit the node, and colonize distant organs in mice - Pereira, Ethel R; Kedrin, Dmitriy; Seano, Giorgio; Gautier, Olivia; Meijer, Eelco F J; Jones, Dennis; Chin, Shan-Min; Kitahara, Shuji; Bouta, Echoe M; Chang, Jonathan; Beech, Elizabeth; Jeong, Han-Sin; et al. (Science (American Association for the Advancement of Science), 2018)
Lymph node metastases in cancer patients are associated with tumor aggressiveness, poorer prognoses, and the recommendation for systemic therapy. Whether cancer cells in lymph nodes can seed distant metastases has been a subject of considerable debate. We studied mice implanted with cancer cells (mammary carcinoma, squamous cell carcinoma, or melanoma) expressing the photoconvertible protein Dendra2. This technology allowed us to selectively photoconvert metastatic cells in the lymph node and trace their fate. We found that a fraction of these cells invaded lymph node blood vessels, entered the blood circulation, and colonized the lung. Thus, in mouse models, lymph node metastases can be a source of cancer cells for distant metastases. Whether this mode of dissemination occurs in cancer patients remains to be determined.